2017
DOI: 10.1038/cr.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

Existing drugs as broad-spectrum and potent inhibitors for Zika virus by targeting NS2B-NS3 interaction

Abstract: Recent outbreaks of Zika virus (ZIKV) highlight an urgent need for therapeutics.The protease complex NS2B-NS3 plays essential roles during flaviviral polyprotein processing, and thus represents an attractive drug target. Here, we developed a split luciferase complementation-based high-throughput screening assay to identify orthosteric inhibitors that directly target flavivirus NS2B-NS3 interactions. By screening a total of 2 816 approved and investigational drugs, we identified three potent candidates, temopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
281
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(294 citation statements)
references
References 74 publications
12
281
0
1
Order By: Relevance
“…Indeed, niclosamide treatment www.nature.com/scientificreports www.nature.com/scientificreports/ during the first 6 h of infection reduced DENV replication in BHK-21 cells harbouring dengue replicons to a level comparable to that of ribavirin, suggesting that the drug affects viral RNA replication and/or translation independent of its effect on entry, membrane fusion and genome release. Furthermore, we provide evidence that niclosamide impairs the proteolytic activity of DENV NS2B-NS3, which is essential for the initiation of www.nature.com/scientificreports www.nature.com/scientificreports/ viral replication and may explain its effects on DENV genome replication and/or translation, strengthening the findings of Li et al 44 . However, these findings are somewhat contradictory to the results reported by Kao et al 41 , which, using a replicon-based assay, indicated that niclosamide had no effect on DENV genome replication.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, niclosamide treatment www.nature.com/scientificreports www.nature.com/scientificreports/ during the first 6 h of infection reduced DENV replication in BHK-21 cells harbouring dengue replicons to a level comparable to that of ribavirin, suggesting that the drug affects viral RNA replication and/or translation independent of its effect on entry, membrane fusion and genome release. Furthermore, we provide evidence that niclosamide impairs the proteolytic activity of DENV NS2B-NS3, which is essential for the initiation of www.nature.com/scientificreports www.nature.com/scientificreports/ viral replication and may explain its effects on DENV genome replication and/or translation, strengthening the findings of Li et al 44 . However, these findings are somewhat contradictory to the results reported by Kao et al 41 , which, using a replicon-based assay, indicated that niclosamide had no effect on DENV genome replication.…”
Section: Discussionsupporting
confidence: 84%
“…An HTS assay was developed to test compounds that inhibit the interaction between NS3 and the NS2B N-terminal fragment [62]. Then, a library of FDA-approved drugs and investigational drugs (2816 drugs) was screened using this assay, and 23 compounds produced an IC 50 below 15 mM, of which 12 were considered PAINS.…”
Section: Ns2b-ns3 Protease Inhibitorsmentioning
confidence: 99%
“…(a) Envelope glycoprotein inhibitor: nanchangmycin (IC 50 = 0.1 mM) [48]. (b) NS2B-NS3 protease inhibitors: temoporfin (IC 50 = 1.1 mM) [62] and NSC157058 (IC 50 = 0.82 mM) [66]. (c) NS3 helicase inhibitor: suramin (EC 50 = 0.42 mM), which was tested only in a cell-based assay in ZIKV [75].…”
Section: Ns2b-ns3 Protease Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although further studies are needed to evaluate their antiviral efficacy in vivo, they also represent promising candidates for anti-ZIKV repurposing. Finally, structure-based in silico screenings, followed by in vitro and in vivo experimental studies, led to the identification of another antibiotic, novobiocin, and other FDA-approved drugs (including niclosamide and temoporfin), as novel inhibitors of ZIKV that act by targeting the NS3/NS2B protease [11,12]. In another study, nanchangmycin, a polyether of bacterial origin, blocked ZIKV infection in different cell lines as well as in ex vivo midbrain neuron-glia mixed cultures from embryonic mice [13].…”
Section: Drug Repurposing For Rna Virus Infectionsmentioning
confidence: 99%